Effect of silanized sisal fiber on thermo-mechanical properties of reinforced epoxy composites. (June 2020) - Mughal, M Moeez; Akhtar, M Wasim; Baloch, M Moazam; Memon, Muddassir Ali; Syed, Junaid Ali; Kim, Jong Seok
An effective method was adopted to improve the thermo-mechanical properties of the epoxy composite by functionalization of the sisal fiber. Initially, a neat sisal fiber was acetylated with molar solution of acidic mixture (0.5:1 of HNO3 :H2 SO4 ) that removed the content of lignin and hemicellulose and increased the crystallinity of the sisal fiber. The acetylated sisal ( a-sisal ) fiber was further treated with 3-aminpropyltriethoxy silane to graft the silanol moieties on sisal fiber. The functionalization of the sisal fiber with 3-aminpropyltriethoxy silane exhibits the strong interaction with epoxy, resulting in homogenous dispersion of the sisal fiber in epoxy. The composite possesses great enhancement in thermal and mechanical properties. The tensile strength in functionalized sisal epoxy composite ( CP-f-Sisal ) was significantly enhanced up to 23% in comparison to non-functionalized sisal epoxy composite ( CP-n-Sisal ) by adding 15 wt.% of the sisal fiber. In addition, the functionalized sisal epoxy composite ( CP-f-sisal ) shows better thermal stability as compared to non-functionalized sisal epoxy composite ( CP-n-sisal ). Similar results are attributed by investigating the kinetics of thermal stability parameters that include activation energy and integral procedure decomposition temperature.